2018
DOI: 10.1159/000493568
|View full text |Cite
|
Sign up to set email alerts
|

Multiparameter Flow Cytometry Identification of Neoplastic Subclones: A New Biomarker in Monoclonal Gammopathy of Undetermined Significance and Multiple Myeloma

Abstract: Multiparameter flow cytometry (MFC)-based clonality assessment is a powerful method of diagnosis and follow-up in monoclonal gammopathy of undetermined significance (MGUS) and multiple myeloma (MM). However, the relevance of intraclonal heterogeneity in immunophenotypic studies remains poorly understood. The main objective of this work was to characterize the different immunophenotypic subclones in MGUS and MM patients and to investigate their correlation with disease stages. An 8-color MFC protocol with 17 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…As the second generation of the Euroflow PCD protocol contains a restricted number of markers, combination of backbone markers with other MoAbs in Euroflow settings is possible, to cover a wide phenotypic PC profile in specific cases, such as PCL. This can further elucidate its behaviour and the clinical impact of the PCL immunophenotypic profile 33,52 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the second generation of the Euroflow PCD protocol contains a restricted number of markers, combination of backbone markers with other MoAbs in Euroflow settings is possible, to cover a wide phenotypic PC profile in specific cases, such as PCL. This can further elucidate its behaviour and the clinical impact of the PCL immunophenotypic profile 33,52 …”
Section: Discussionmentioning
confidence: 99%
“…This can further elucidate its behaviour and the clinical impact of the PCL immunophenotypic profile. 33,52 Since sPCL evolves from existing MM, significantly longer median OS of pPCL than sPCL was expected. Other groups also found similar data of longer median OS in pPCL than sPCL.…”
Section: Discussionmentioning
confidence: 99%
“…However the application of flow cytometry in MM is mainly used in monitoring of minimal residual disease (Flores- Montero et al, 2017;Rasche et al, 2019;Roshal, 2018;Waldschmidt et al, 2018). However, it would be most valuable to PCs and CD27, CD19 and CD56 to distinguish between normal and abnormal PCs according to existing literature (Alaterre et al, 2018;Flores-Montero et al, 2016;Tarín et al, 2019). This abnormal phenotype of BM plasma cells has been used to study minimal residual disease in MM, and it has been shown that the persistence of abnormal immunophenotype PC in BM after treatment is associated with poor clinical outcomes (Davies et al, 2002;Galtseva et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, progression from MGUS to MM is characterized by reduced sub-clones’ variability with the appearance of a dominant clone. The immunophenotype profile was similar between MGUS and MM, however loss of CD27 and an increase in CD81 was noted in the dominant clone of relapsed patients [ 93 ]. A further study linked CD81 with differentiation of MM cells and identified CD19+/CD81− expressing MM cells as a more immature subset of PC [ 94 ].…”
Section: Introductionmentioning
confidence: 99%
“…CD27 expression on T-cells acts as a co-stimulatory receptor, while binding of CD70 to CD27 on B-cells promotes differentiation to PC [ 97 ]. Several studies have shown that loss of CD27 expression characterizes progression to MM and less favorable prognosis [ 93 , 98 , 99 ]. Chu et al investigated the significance of CD27 expression in newly diagnosed MM patients and found that CD27-negative disease had higher adverse risk characteristics, including higher PC burden and advanced stage.…”
Section: Introductionmentioning
confidence: 99%